Aplicação da eletroforese capilar com detecção condutométrica sem contato no controle de qualidade de formulações farmacêuticas contendo aspirina ou dipirona em combinação com outros princípios ativos - Marra, Mariana Cardoso (2014)
In the present work capillary electrophoresis with contactless capacitive coupled conductivity detection (CE-C4D) was used for the development of fast methods for quality control of medicines. The background electrolyte (BGE) composed of 20 mmol L-1 2-amino-2-(hydroxymethyl)propane-1,3-diol (TRIS) and 10 mmol L-1 3,4-dimethoxycinnamic acid (DMX), pH 8.4, was used for the analysis of two pharmaceutical formulations containing: (a) dipyrone (DIP) + caffeine (CAF); (b) acetylsalicylic acid (AAS) + CAF. Another BGE composed of 12 mmol L-1 triethanolamine (TEA) and 10 mmol L-1 DMX (pH 8.5) was used for the analysis of pharmaceuticals samples containing: (a) DIP + scopolamine (ESC); (b) DIP + CAF + orphenadrine (ORF); (c) DIP + CAF + mepyramine (MEP) + ascorbic acid (AA). All proposed analytical methods are fast, with duration equal to or less than 1 minute. In addition, the degradation products from DIP (methylamine) and AAS (salicylic acid) were also detected. Capillary electrophoresis coupled to mass spectrometry (CE-MS) was used in order to confirm the formation of methylamine (compound detected for the first time). In the determination of CAF, DIP, AAS, and AS, the RSDs (n = 10) calculated were less than 6%, 0.6% and 6%, for peak area, migration time and resolution, respectively. In the determination of DIP, CAF, ESC, ORF, MEP, and AA, the SDR (n = 10) calculated were less than 4%, 2% and 5%, for peak area, migration time and resolution, respectively. The calibration curves for all quantified species presented correlation coefficients above 0.993. The results obtained with the proposed method for analysis of commercial pharmaceutical samples containing CAF + AAS or CAF + DIP were compared with those obtained by HPLC. The calculated t-values (paired t-Student test), with confidence level of 95%, were smaller than the critical value (2.78, n = 3) in all the analyses, which indicates that there were no significant differences between the results found with the proposed method and HPLC. In addition, the proposed method presented satisfactory results in the recovery test (92% to 103%) for samples containing DIP and the other active ingredients (CAF, ESC, MEP, ORF e AA).